Chronological Change of Resistance to β-Lactams in Salmonella enterica serovar Infantis Isolated from Broilers in Japan - Chuma, Takehisa; Miyasako, Daisuke; Hesham, Dahshan; Takayama, Tomoko; Nakamoto, Yuko; Shahada, Francis; Akiba, Masato; Okamoto, Karoku (Frontiers in Microbiology, 2013)
Epidemiologic surveillance study was conducted in southern Japan to determine the antimicrobial resistance phenotypes and characterize the β-lactamase genes and the plasmids harboring these genes in Salmonella enterica serovar Infantis (S. Infantis) isolates from broilers. Between January, 2007 and December, 2008, a total of 1,472 fecal samples were collected and examined at the Laboratory of Veterinary Public Health, Kagoshima University, Japan. In 93 (6.3%) isolates recovered, 33 (35.5%) isolates showed resistance to cefotaxime, an extended-spectrum cephalosporin (ESC), conferred by TEM-20, TEM-52 and CTX-M-25 extended-spectrum β-lactamases (ESBLs). In addition to ESC-resistance, eight (8.6%) isolates exhibited resistance to cefoxitin mediated by CMY-2 AmpC β-lactamase. Plasmid analysis and polymerase chain reaction replicon typing revealed the blaTEM-20 and blaCMY-2 genes were associated with IncP plasmids, blaTEM-52 was linked with a non-typable plasmid and blaCTX-M-25 was carried by an IncA/C plasmid. Non- β-lactam resistance to streptomycin, sulfamethoxazole and oxytetracycline encoded by the aadA1, sul1 and tet(A) genes, respectively, was found in 86 (92.5%) isolates. Resistance to kanamycin and ofloxacin was exhibited in 12 (12.9%) and 11 (11.8%) isolates, respectively, the former was mediated by aphA1-Iab. These data indicate that S. Infantis isolates producing ESBLs and AmpC β-lactamase have spread among broiler farms in Japan. These data demonstrated that the incidence of ESC-resistant S. Infantis carrying blaTEM-52 remarkably increased and S. Infantis strains harboring blaCMY-2, blaTEM-20 or blaCTX-M-25 genes emerged from broilers in Japan for the first time in 2007 and 2008.